Association between life's essential 8 and frailty status among cancer survivors in the United States: a cross-sectional analysis - Xiuxiu Qiu; Qidong Wu; Yiyi Zhang; Yingjie Zhu; Ming Yang; Li Tao (BMC, 2024)
Abstract Background Frailty not only affects disease survival but also impacts the long-term function and quality life of all adults diagnosed with and/or treated for cancer.The American Heart Association has introduced Life's Essential 8 (LE8) as a novel metric for assessing cardiovascular health. Currently, LE8's application in evaluating the frailty of cancer survivors remains unreported. This research seeks to explore the connection between LE8 scores and frailty levels in cancer survivors across the United States, thereby addressing a significant void in existing studies. Methods This study analyzed data from cancer survivors enrolled in the National Health and Nutrition Examination Surveys (NHANES) spanning the years 2005 to 2018, providing a comprehensive dataset. Multivariable logistic regression models were used to examine the linkage between LE8 rankings and frailty condition in cancer survivors. Furthermore, the study delved deeper into this correlation using restricted cubic spline (RCS) curves and subgroup analyses. Results In the fully adjusted model, an increased LE8 level was closely associated with a reduced odds ratio of frailty among cancer survivors, with an OR of 0.95 (95% CI: 0.94-0.96, p < 0.0001).This pattern persisted across different categorizations of LE8 into low, moderate, and high groups, demonstrating a consistent trend. The analysis revealed a non-linear relationship between LE8 scores and frailty status, further supporting a straightforward association (p-value for non-linearity = 0.0729). Conclusion Studies have found that the higher the LE8 score, the less likely a cancer patient is to develop debilitating symptoms.This indicates that the LE8 scores may provide an opportunity for interventions aimed at improving the prognosis of cancer patients.